SURVEI TINGKAT MOTIVASI SISWA DALAM MENGIKUTI PEMBELAJARAN PENDIDIKAN JASMANI PADA MASA PEMBELAJARAN JARAK JAUH DI SDN 032 TILIL KOTA BANDUNG - Agam Geofani Akbar, - (2021)
The problem in this study is that the students' motivation in participating in physical education learning during the distance learning period is slightly different in usual, because each student's ability in the field of technology and the problem of student economic factors is different to take physical education learning during the distance learning period. Therefore, researchers wanted to know the level of student motivation in participating in physical education learning during distance learning at SDN 032 Tilil Bandung City. This research uses descriptive research and the type of research is a survey, the data collection technique uses a questionnaire, the sample studied is all class 6 SDN 032 Tilil Bandung, totaling 125 students with simple random sampling techniques and the data analysis technique using quantitative descriptive expressed in percentage . The results showed that the motivation of students in participating in physical education learning during distance learning at SDN 032 Tilil Bandung was in the "Very High" category of 10.91% (6 students), "High" of 23.64% (13 students). ), "Medium" amounted to 32.73% (18 students), "Low" 29.09% (16 students), "Very Low" 3.69% (2 students). It can be concluded that the motivation of grade VI students in participating in Physical Education learning during distance learning at SDN 032 Tilil Kota Bandung falls into the "Medium" category.